Transcriptional Down-Regulation of Major Histocompatibility Complex as a Possible Pathogenesis for Meniere's Disease - Choi, Kwang-Dong; Oh, Eun Hye; Kim, Hyun Sung; Kim, Hyang-Sook; Park, Ji-Yun; Choi, Seo Young; Choi, Jae-Hwan (Frontiers in Neurology, 2022)
Objectives This study aimed to determine the underlying pathogenesis of Meniere's disease (MD) using transcriptome analysis. Methods Total RNA was extracted from the peripheral blood mononuclear cells of 39 patients with MD and 39 controls. Through microarray analysis for nine patients and controls, the differentially expressed genes (DEGs) of those two groups were screened based on cut-off criteria (|fold changes| > 2.0 and adjusted p-value < 0.05). The functional enrichment analysis of DEGs was performed using Gene Ontology (GO). Results There were 996 DEGs identified in the MD group: 415 were upregulated and 581 were downregulated. A functional enrichment analysis indicated that the downregulated DEGs were significantly enriched in terms related to immune system processes. Among them, 17 genes were enriched in terms for the major histocompatibility complex (MHC) protein complex, and the relative messenger RNA (mRNA) levels of three markedly downregulated DEGs [fold changes < −5: human leukocyte antigen (HLA)-DMA, HLA-DRB1, and HLA-DPB1] were significantly decreased in another 30 patients with MD compared with normal controls by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). However, there were no correlations between the expression levels of these three genes and clinical data, such as age, onset age, time course, or hearing threshold. Conclusions Our transcriptome analysis showed that the downregulated DEGs in MD were mainly associated with the immune system pathways including the MHC protein complex in MD. Remarkably, a breakdown in immunological tolerance mediated by MHC class II may contribute to the MD development, which has implications for targeted treatment.